John Stainer: a life in music - Dibble, Jeremy (Woodbridge The boydell press, 2007)
"The thoroughness of the research is impressive, based on profusion of sources, many of them little used until now.... A text that carries great authority, plus (almost equally important) a new and generously annotated list of Stainer's works both musical and literary. At last, Stainer has got his due, once and for all.'"NICHOLAS TEMPERLEY, Professor of Music Emeritus, University of Illinois. One of the most important musicians of the Victorian era, Stainer is known for his considerable influence as a composer of Anglican liturgical music, and his corpus of secular works - madrigals and songs - presents many surprises. He was a brilliant organist, a fine scholar, theorist, pedagogue and teacher - multifarious attributes which this study elucidates and understands as part of his wider musical personality. Stainer's life is a story of extraordinary social mobility. From lowly origins he rose to become organist of St Paul's Cathedral and Professor of Music at Oxford. Yet after his premature death in 1901 he suffered almost immediate neglect except for the popularity of a handful of works, among them I saw the Lord/I>and The Crucifixion. In rehabilitating Stainer and the crucial contribution he made to musical life, this book examines the breadth of his work as a composer, and the important role he played in the regeneration of sacred and secular musical institutions in Victorian Britain. JEREMY DIBBLE is Professor of Music at Durham University. His previous books include studies of Parry and Stanford and he is the author of numerous articles on British music. He is currently working on a dictionary of hymnology.